Marketing of Shrimp through e_HUB in West and East Godavari Districts of Andhra Pradesh: An Aquachoupal Model - Mahalakshmi, P; Krishnan, M (Fishery Technology, 2025)
A study was undertaken in and around West and East Godavari districts of Andhra Pradesh to analyse the ongoing activities of an aquachoupal model, to work out the usage patterns of aquachoupal services, to analyse the farmers’ perception on the model, to observe constraints if any of the implementation of the aquachoupal and to analyse the suggestions of the farmers for the improvement of the model. Among the various services offered by the aquachoupal, farmers made use of market pricing and customized quality solution facilities frequently. Farmers strongly agreed that the prompt payment and the provision of giving discounted inputs at the farm gate, provide meaningful net economic benefits to farmers. With the information obtained from shrimp farmers, it appears that medium and big farmers are getting more benefits through aquachoupal than small farmers. Among the various constraints, ignorance of farmers about technology in progress was ranked as the major constraint followed by lack of awareness about services provided by the aquachoupal and lack of interaction with shrimp farmers association. Overall assessment of the aquachoupal model in the study area and the improvement of the initiative are also discussed.